The development of sharing economy in the Czech Republic : Quantitative media analysis - Krivošová, Martina; Lukeš, Martin, 1976-; Dvouletý, Ondřej; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
The thesis analyses the development of sharing economy in the Czech Republic over the last decade (2008-2017) as presented by the Czech media. More than 8 000 messages sourced from print media, television and radio were subjected to quantitative media analysis in order to explain when and how this phenomenon emerged in the Czech Republic. Additional set of 223 message was subjected to content analysis to understand the relevance of this phenomenon and the way it is presented to the Czech audience. Based on the quantitative media analysis it was concluded that the term “sharing economy” was adopted by the Czech journalists only around the year 2015. However, even now the term is not widely adopted. In most of the cases, the term is not used when the message refers to some sharing economy company. Negative attributes are more often associated with the sharing economy than its positive impact. This can be largely influenced by the fact that the term “sharing economy” is in 70% of case associated with companies Uber and Airbnb, who have recently earned negative media coverage due to the avoidance of regulations and tax evasions.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses